ELABORATION OF A PPE MANAGEMENT PROCEDURE FOR HOMECARE IN COVID19 CONTEXT - Rui Pedro Silva; José Luis Sepúlveda; Michel Costa; Carla Ferreira; Eliana Carneiro; Daniela Fernandes (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: To describe the process of elaboration, by the team of the Community Care Unit Vallis Longus, of a procedure for the handling of Personal Protective Equipment (PPE) during homecare visits (HCV) within the scope of COVID19. Method: The preparation of the PPE handling procedure in the context of HCV followed the following steps sequentially: a) review of the available literature; b) team discussion on the respondent's viability in the previous point; c) theoretical elaboration of the procedure; d) practical test of the procedure; e) preparation of the final version of the procedure; f) development of a video demonstrating the procedure. Results and discussion: The elaboration of the PPE management procedure in the context of the HV implies the assessment of its viability, both in terms of the necessary material resources and in terms of the use of the procedure in the real context of home care provision. The described phases made it possible to adapt what was described in the literature, so that it could be fully implemented in the daily organization of the unit and, consequently, in the direct provision of care. The production of a video facilitated the training actions related to the procedure, which mostly acquired a virtual character due to the pandemic COVID19. Conclusion: The context of the COVID19 pandemic created the need to review the PPE handling procedures inherent in HV to prevent the spread of infection. The development, in a discussion team, of a procedure based on the combination of the literature and the practical feasibility of its implementation allowed to put into operation an effective and sustainable PPE management model.